PENGARUH GREEN HUMAN RESOURCE MANAGEMENT (GHRM) TERHADAP KINERJA ORGANISASI DAN KESADARAN LINGKUNGAN DI PUSAT KEUANGAN TNI - Prananingrum, Enggar Oktarina; Faeni, Dewi Puspaningtyas (SINERGI : Jurnal Riset Ilmiah, 2025)
This research aims to comprehensively analyze the influence of Green Human Resource Management (GHRM) on organizational performance and environmental awareness at the Indonesian National Armed Forces Finance Center. GHRM is perceived as a strategic approach integrating environmental sustainability principles into the entire human resource management cycle, including recruitment, training, performance evaluation, and reward systems. Using a quantitative approach, the study involved 120 personnel who responded to a Likert scale questionnaire (1–5). Data analysis employed multiple linear regression with validity tests, reliability tests, t-tests, and F-tests. Simulation results reveal that GHRM has a positive and significant effect on organizational performance (β=0.482, p<0.05) and environmental awareness (β=0.537, p<0.05). These findings highlight the importance of implementing GHRM in the military environment as a means to achieve optimal performance while fostering a culture of environmental consciousness